Development of Project-Based Critical Thinking Process Instruments in the Physics Learning Assessment Course - Agustini, Sri; Arafah , Kaharuddin; Helmi; Rezki Hamzah, Ria (Physics Education, 2025)
This research aims to develop a project-based assessment instrument to measure students' critical thinking processes in the Physics Learning Assessment course. The development of this instrument uses the ADDIE learning design model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The Analysis stage is carried out to identify assessment needs, while the Design and Development stage is used to design and develop a valid project-based assessment instrument with a validity coefficient of 1.00 using Gregory analysis. The critical thinking instrument uses 6 aspects, namely Verbal Reasoning, Argument Analysis, Hypothesis Testing, Uncertainty Analysis, Problem Solving and Decision Making Furthermore, the Implementation stage is carried out through instrument trials on students obtained results that students are in high category with a range of total score between 15-19. Furthermore, The students perceptions has the best in terms of verbal ability and at least in the aspect of uncertainty analysis, and the Evaluation stage is used to analyze and improve the instrument at each step based on the results of the implementation.